Unifikasi Kalender Hijriah Nasional Menurut Perspektif Muhammadiyah dan Nahdlatul Ulama - Husna, Amirah Himayah (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2022)
Abstract Basically, this research comes from the arrangement for beginning of the month to come up diversity in establishment. This problem can’t be separated with its historical thinking deveploment of Islam that surrrounded by various ideology this then made many differences. In fact, these differences happened in Indonesia, especially Muhammadiyah and Nahdatul Ulama (NU). There are organizations that use hisab method and there are others that use ru’yah method in deciding the beginning of month. The problematic between hisab and ru’yah is always viral and even able to make muslims fight with each other because each of these organizations in the society are claim the truth. This is because, there is no agreement related to it. To realize the unity of the determination of the beginning of the month there must be one madzhab that becomes the authority, as in the rule of  "the decision of the judge (State) to erase differences". The relevance of the unification of the Islamic calender can be seen from point of view from two organization and can be done through astronomy expert in Indonesia based on the authority of the Ministry of Religion of The Republic of Indonesia for take the policy on this problematic. Keywords: The Arrangement, The Different, Muhammadiyah, NU, Islamic Calender, The Unification